The role of shoope's live streaming feature as digital marketing for online shop Kalukalu.id - Harun Hamnoer; Femi Oktaviani (Sean Institute, 2024)
Digital marketing also makes it easier for business people to monitor and provide all the needs and desires of potential consumers, and on the other hand potential consumers can search for and obtain product information just by browsing cyberspace, thus making the search process easier (Dedi, Rahmi, & Shandy, 2018). Of course, this existence cannot be avoided due to the rapid development of technology, especially in this era. Shopee LIVE is a feature that allows you to create live streaming sessions and promote shops & products directly to buyers. In the context of the research explained previously, the researcher focused his research on the role of the Shopee Live Streaming Feature as Digital Marketing for the Kalukalu.Id Online Shop, the role of the live streaming feature in Shopee E-Commerce as a form of new adaptation of marketing communications during the pandemic for the Kalukalu.id brand) . As a medium for disseminating information and education, distribution media and media that influences audiences by segmenting permanent and potential consumers of Kalukalu.id. The aim of this research is how to process information from kalukalu.id to consumers, the selection of features in live streaming chosen by kalukalu.id, and the role of live features in maintaining the flow of communication on Instagram social media as a medium for buying and selling transactions.